Anti-Inflammatory and Antibacterial Activity of the Chitosan/Chlorhexidine Gel Commercial Preparation for Postexodontia Treatment: An In Vitro Study - Torres-Rosas, Rafael; Torres-Gómez, Nayely; Moreno-Rodríguez, Adriana; García-Contreras, René; Argueta-Figueroa, Liliana (European Journal of Dentistry, 2020)
Objective The present study aimed to assess in vitro the antibacterial activity, cytotoxicity, and the expression of prostaglandin E2 (PGE2) of Bexident post topical gel (BP).Materials and Methods The broth dilution test was performed to analyze the antimicrobial activity of BP against Staphylococcus aureus, Escherichia coli, and Streptococcus mutans. Minimal bactericidal concentrations (MBCs) and minimal inhibitory concentrations (MICs) were assessed. Cytotoxic activity was performed by the MTT (tetrazolium dye) method on human gingival fibroblast (HGF), human bone cells (HBC), and human pulp cells (HPC) (from primary cell culture) and HGF-1 from American Type Culture Collection. The expression of PGE2 produced by RAW 264.7 cells was determined by ELISA utilizing an Enzyme Immuno-Assay Kit.Statistical Analysis Shapiro–Wilks normality test and Mann–Whitney U test were performed for all data.Results The MBCs of BP for S. aureus, E. coli, and S. mutans were found at 25, 50, and 12.5%, respectively. The MICs for the same strains were found at 12.5, 25, and 3.125%. The CC50 of BP gel for HBC, HPC, and HGF, and HGF-1 were 12.5 ± 1.09, 0.37 ± 0.02, 0.35 ± 0.02, and 20.4 ± 0.02%, respectively. The levels of expression PGE2 produced by RAW 264.7 cells treated with IL-1β exhibit an inverse dose-dependent effect on the concentrations of BP gel used.Conclusion Our results indicate that the BP gel has a great antibacterial effect, adequate biocompatibility, showing a decrease in the expression of PGE2 on cells with previously induced inflammation. Due to the above, its use as a healing agent after oral surgery seems to be adequate.
Keywords: chitosan; chlorhexidine; cytotoxicity; antibacterial properties; Bexident post